Dependence of evaporation losses on petrol quality - Chernyak, Larisa; Boychenko, Sergey; Fedorovich, Ludmila; Novikova, Valentina; Prentkovskienė, Rasa; Pukalskas, Saugirdas (Transport, 2010)
The paper deals with the interrelation between evaporation losses and automobile petrol quality and presents the results of research on modern petrol. It has been established that evaporation leads to an increase in heavy hydrocarbon concentration in petrol composition adversely affecting its quality and operational properties at the excess of permissible concentration.First published online: 10 Feb 2011